Methodological Recommendations to Control for Factors Influencing Dream and Nightmare Recall in Clinical and Experimental Studies of Dreaming - Putois, Benjamin; Leslie, Wendy; Asfeld, Claire; Sierro, Caroline; Higgins, Susan; Ruby, Perrine (Frontiers in Neurology, 2020)
In order to ensure robust relationships between the dependent and independent variables in clinical dream/nightmare studies, the major factors which influence the frequency of reported dreams must be controlled. This article sets out methodological recommendations to both researchers seeking to ensure the equivalence of experimental groups of participants in group-matching designs, and to clinicians who wish to check that any change in frequency of reported nightmares over the course of a psychological or a pharmacological intervention is not caused by factors other than the experimental treatment itself. The main factors influencing the frequency of dream recall are presented: demographic variables, psychological characteristics, pathological dimensions and substance consumption. A series of questionnaires is proposed for easily measuring these control variables.